Growth and porosity of C-S-H phases using the sheet growth model. (March 2020) - Nguyen-Tuan, Long; Etzold, Merlin A.; Rößler, Christiane; Ludwig, Horst-Michael
Abstract: Realistic modelling of the meso-structural development of concrete enables the prediction of material properties. The present study develops and deploys a computer model to simulate the growth and porosity of calcium silicate hydrate (C-S-H) phases. The growth kinetics is governed by a simplified function that can be related to dissolution and precipitation processes. Simulated C-S-H structures reproduce closely observations from experiments. This is achieved by combining different growth mechanisms for C-S-H sheets such as planar, defective, and layering growth. Most initial conditions are directly taken from scanning electron microscopy observations. The model leads to structures with pore sizes in the range associated with interlayer, gel and capillary pores. Model outputs such as pore size distribution, growth rate, and the temporal development of the pore space agree qualitatively with experimental data.